Virtuous bodies the physical dimensions of morality in Buddhist ethics - Mrozik, Susanne; Oxford eBooks (Oxford : Oxford University Press, 2007)
Investigating the diverse roles bodies play in Buddhist ethical development, this book takes an influential early medieval Indian Mahayana Buddhist text (Nullantideva's 'Compendium of Training') as a case study.
Description based on print version record.
Includes bibliographical references and index.
Keywords: d; Human body -- Religious aspects -- Buddhism; Buddhist ethics; Electronic books